Correction to: Synthesis and biological evaluation of some 4-aminoquinoline derivatives as potential antitubercular agents - Shankar Alegaon; Kamlesh Kashniyal; Sanket Kuncolienkar; Rohini Kavalapure; Preeti Salve; Mahesh Palled; Shailendra Suryawanshi; Sunil Jalalpure (SpringerOpen, 2020)
Following publication of the original article [1], the authors reported an error in one of the authors' names.